2017
DOI: 10.1093/bmb/ldx006
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of prolotherapy in treating knee osteoarthritis in adults: a systematic review

Abstract: Future research should focus on larger sample size, standardization of treatment protocol and basic science evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Often included in the regenerative therapies, prolotherapy is a relatively uncommon treatment for treating K-OA with very little scientific evidence. However, as a relatively simple and inexpensive treatment modality with a high safety profile, prolotherapy is something that could easily be performed in the primary care setting and is thus worth our consideration [67][68][69][70]. A hypertonic irritating solution is used to treat the affected knee and can be injected both periand intra-articular.…”
Section: Prolotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Often included in the regenerative therapies, prolotherapy is a relatively uncommon treatment for treating K-OA with very little scientific evidence. However, as a relatively simple and inexpensive treatment modality with a high safety profile, prolotherapy is something that could easily be performed in the primary care setting and is thus worth our consideration [67][68][69][70]. A hypertonic irritating solution is used to treat the affected knee and can be injected both periand intra-articular.…”
Section: Prolotherapymentioning
confidence: 99%
“…A small study published in 2017 showed no significant changes in WOMAC and VAS scores between patients treated with either intra-or periarticular prolotherapy [67]. ere are some variabilities in the method of peri-articular administration of the dextrose, but the two key techniques are either Lyftogt's technique or Hackett's technique [69]. In Lyftogt's technique, dextrose is injected into subcutaneous tissues.…”
Section: Prolotherapymentioning
confidence: 99%
“…Nevertheless, the clinical outcomes including pain, joint stiffness and physical function were also improved. This nding indicated that the hypertonic dextrose intra-articular injections for OA knee patients have a clinically effect lasting from weeks to months post treatment [20,21].…”
Section: Discussionmentioning
confidence: 89%
“…Dextrose prolotherapy is an alternative to surgery for knee osteoarthritis patients. The potential mechanism of dextrose prolotherapy relevant pain-intensity reduction is associated with the hyperpolarization of nociceptive pain bers by opening the potassium channels [21]. Prolotherapy simulates the normal tissues' healing and repair response, which includes the three stages of in ammation, proliferation, and tissue remodeling [23].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Studies have shown that prolotherapy is efficacious in the management of knee osteoarthritis and tendinopathy. 10,11 We agree that the evidence to support its use in the context of RCLs is less robust Hong Kong Med J 2018;24:538-9 DOI: 10.12809/hkmj187528…”
Section: Dextrose Prolotherapy For Rotator Cuff Lesions: the Challengmentioning
confidence: 94%